Influence of Ta'awun (Mutual Cooperation) among community members in enhancing zakat compliance behaviour - Mhd. Sarif, Suhaimi; Ismail, Yusof (Pusat Pungutan Zakat (PPZ-MAIWP), 2022)
Advocacy among community members enhances compliance behaviour. The influence of ta’awun (mutual cooperation) among community members reinforces compliance behaviour. Zakat institutions have been persistent in advocating zakat compliance behaviour. It is believed that peer advocacy with ta’awun (mutual cooperation) is more influential in increasing zakat compliance behaviour. The main objective of the study is to explore the influence of ta’awun (mutual cooperation) among community members in enhancing zakat compliance behaviour. This study uses qualitative research through focus group discussion via a community’s WhatsApp group. The study managed to obtain feedback from four advocates of social advocacy for zakat. The advocates argued that the influence of ta’awun (mutual cooperation) among community members can be achieved using casual sharing, educational, and practical approaches. The blended approach complements ta’awun among community members in enhancing zakat compliance behaviour. Results of a convenience sampling, and moreover of small size provide insights into a specific context which may not be generalizable in other community contexts. Future research should strongly consider using case study method with different community contexts so that readers could be offered insights from different contexts. Keywords: ta’awun, zakat obligation, zakat compliance behaviour.